Skin permeability barrier formation by the ichthyosis-causative gene FATP4 through formation of the barrier lipid [omega]-O-acylceramide - Yamamoto, Haruka; Chamulitrat, Walee (Proceedings of the National Academy of Sciences of the United States of America, 2020)
The epidermis-specific lipid acylceramide plays a pivotal role in the formation of the permeability barrier in the skin; abrogation of its synthesis causes the skin disorder ichthyosis. However, the acylceramide synthetic pathway has not yet been fully elucidated: Namely, the acyl-CoA synthetase (ACS) involved in this pathway remains to be identified. Here, we hypothesized it to be encoded by FATP4/ACSVL4, the causative gene of ichthyosis prematurity syndrome (IPS). In vitro experiments revealed that FATP4 exhibits ACS activity toward an ω-hydroxy fatty acid (FA), an intermediate of the acylceramide synthetic pathway. Fatp4 knockout (KO) mice exhibited severe skin barrier dysfunction and morphological abnormalities in the epidermis. The total amount of acylceramide in Fatp4 KO mice was reduced to ∼10% of wild-type mice. Decreased levels and shortening of chain lengths were observed in the saturated, nonacylated ceramides. FA levels were not decreased in the epidermis of Fatp4 KO mice. The expression levels of the FA elongase Elovl1 were reduced in Fatp4 KO epidermis, partly accounting for the reduction and shortening of saturated, nonacylated ceramides. A decrease in acylceramide levels was also observed in human keratinocytes with FATP4 knockdown. From these results, we conclude that skin barrier dysfunction observed in IPS patients and Fatp4 KO mice is caused mainly by reduced acylceramide production. Our findings further elucidate the molecular mechanism governing acylceramide synthesis and IPS pathology.